1994
DOI: 10.1038/367657a0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of E. coli Ffh/4.5S ribonucleoprotein and FtsY mimics that of mammalian signal recognition particle and its receptor

Abstract: The mechanism of protein translocation across the endoplasmic reticulum membrane of eukaryotic cells and the plasma membrane of prokaryotic cells are thought to be evolutionarily related. Protein targeting to the eukaryotic translocation apparatus is mediated by the signal recognition particle (SRP), a cytosolic ribonucleoprotein, and the SRP receptor, an endoplasmic reticulum membrane protein. During targeting, the 54K SRP subunit (M(r) 54,000; SRP54), a GTP-binding protein, binds to signal sequences and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(225 citation statements)
references
References 26 publications
7
218
0
Order By: Relevance
“…Biochemical studies of the effects of SRP RNA on various components and on the formation and behavior of the Ffh:FtsY targeting complex have shown that SRP RNA, when bound to Ffh, enhances the association and GTPase activity of Ffh and FtsY, 45 and increases dramatically the rate at which GTP-loaded SRP and SR associate and dissociate. 5 The proximity of an external nucleotide-binding pocket to the active center of FtsY and to both nucleotides within the shared catalytic chamber suggests the existence of a direct regulatory interaction between SRP RNA and the active center of the heterodimeric GTPase.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies of the effects of SRP RNA on various components and on the formation and behavior of the Ffh:FtsY targeting complex have shown that SRP RNA, when bound to Ffh, enhances the association and GTPase activity of Ffh and FtsY, 45 and increases dramatically the rate at which GTP-loaded SRP and SR associate and dissociate. 5 The proximity of an external nucleotide-binding pocket to the active center of FtsY and to both nucleotides within the shared catalytic chamber suggests the existence of a direct regulatory interaction between SRP RNA and the active center of the heterodimeric GTPase.…”
Section: Discussionmentioning
confidence: 99%
“…8). In the presence of GTP, Ffh͞4.5S RNA forms a complex with FtsY, leading to a reciprocal stimulation of both GTPases (9)(10)(11). This observation led to the proposal that Ffh and FtsY are GTPase-activating proteins (GAPs) for each other (11).…”
mentioning
confidence: 99%
“…Furthermore, the Ffh/4.5 S RNA complex, having an SRP-like function, was found to bind to FtsY in a GTP-dependent manner [46]. This interaction caused the stimulation of GTP hydrolysis, which signal peptides inhibited [46]. These properties resemble those of the eukaryotic system, suggesting that the E. coli system functions in protein targeting in a similar manner to that of eukaryotic counterparts.…”
Section: Problems Remaining To Be Clarifiedmentioning
confidence: 55%
“…It has been reported that FIh is important for protein translocation in vivo [45]. Furthermore, the Ffh/4.5 S RNA complex, having an SRP-like function, was found to bind to FtsY in a GTP-dependent manner [46]. This interaction caused the stimulation of GTP hydrolysis, which signal peptides inhibited [46].…”
Section: Problems Remaining To Be Clarifiedmentioning
confidence: 95%